Major depression disorder may causally associate with the increased breast cancer risk: Evidence from two‐sample mendelian randomization analyses. (19th July 2022) - Ren, Qian; Luo, Fangxiu; Ge, Sheng; Chen, Peizhan
Abstract: Introduction: Major depression disorder (MDD) has been associated with increased breast cancer risk in epidemiological studies; however, it is still unknown whether this association is causal or not. The aim of this study is to determine the causal relationship between MDD and breast cancer risk. Methods: Two‐sample Mendelian randomization (MR) analyses with 92 single‐nucleotide polymorphisms (SNPs) significantly associated with MDD as instrumental variables (IVs) were performed. Effects of these SNPs on breast cancer in women were estimated in the Breast Cancer Association Consortium (122, 977 cases and 105, 974 controls) using inverse variance weighted (IVW), weighted median and multivariable MR models. Heterogeneity and pleiotropy effects were assessed based on IVW and MR‐Egger regression model, respectively. Results: An 8.7% increased risk of overall breast cancer [odds ratio ( OR ) = 1.087; 95% confidence interval ( CI ) 1.011–1.170; P  = 0.025] per log‐odds ratio increment of MDD risk based on the IVW model was noticed. Similar results were obtained with the multivariable MR model ( OR  = 1.118, 95% CI  = 1.010–1.237; P  = 0.031). An increment but not statistically significant causality association was noticed between MDD and risk of ER+ ( OR  = 1.098, 95% CI  = 0.984–1.227; P  = 0.093) or ER‐ ( OR  = 1.129, 95% CI  = 0.982–1.297; P  = 0.089) breast cancer under multivariable MR model. No significant pleiotropy effects were observed for the IVs in the two‐sample MR studies. Conclusions: The results suggested that a genetic predisposition of MDD is causally associated with overall breast cancer risk; however, the underlying biological mechanisms are worthy of further study. Abstract : Using the two‐sample Medenlian Randomization analysis methods, we found a causal association between major depression disorder and breast cancer risk in women